Transgenic zebrafish model of the C43G human insulin gene mutation - Eames, Stefani C (Wiley-Blackwell, 2012)
AIMS/INTRODUCTION: The human insulin gene/preproinsulin protein mutation C43G disrupts disulfide bond formation and causes diabetes in humans. Previous in vitro studies showed that these mutant proteins are retained in the endoplasmic reticulum (ER), are not secreted and are associated with decreased secretion of wild‐type insulin. The current study extends this work to an in vivo zebrafish model. We hypothesized that C43G‐green fluorescent protein (GFP) would be retained in the ER, disrupt β‐cell function and lead to impaired glucose homeostasis. MATERIALS AND METHODS: Islets from adult transgenic zebrafish expressing GFP‐tagged human proinsulin mutant C43G (C43G‐GFP) or wild‐type human proinsulin (Cpep‐GFP) were analyzed histologically across a range of ages. Blood glucose concentration was determined under fasting conditions and in response to glucose injection. Insulin secretion was assessed by measuring circulating GFP and endogenous C‐peptide levels after glucose injection. RESULTS: The majority of β‐cells expressing C43G proinsulin showed excessive accumulation of C43G‐GFP in the ER. Western blotting showed that C43G‐GFP was present only as proinsulin, indicating defective processing. GFP was poorly secreted in C43G mutants compared with controls. Despite these defects, blood glucose homeostasis was normal. Mutant fish maintained β‐cell mass well into maturity and secreted endogenous C‐peptide. CONCLUSIONS: In this model, the C43G proinsulin mutation does not impair glucose homeostasis or cause significant loss of β‐cell mass. This model might be useful for identifying potential therapeutic targets for proper trafficking of intracellular insulin or for maintenance of β‐cell mass in early‐stage diabetic patients.